Comparison and analysis of burden design methods in blasting: a case study on Sungun copper mine in Iran. (22nd September 2010) - Sereshki, Farhang; Ataei, Mohammad; Hoseinie, Seyed Hadi
In this study, 19 burden designing methods have been analysed for burden design in the Sungun Copper Mine in Iran. Also, economical Optimum Burdens (OBs) have been calculated using the results of actual blastings. The results of mentioned methods and optimum burden have been compared with each other. The comparison shows that the Anderson, Pears, Allsman, Langefors and Energy Transition (ET) methods have very close results to the OB. Also, the results of Fraenkel, Ash, Foldesi and Prillet methods are very different from the OB. Therefore, earlier methods could not be used in burden designing for open pit mines.